Program Mubaligh Hijrah Nasional Santri Muallimin Muhammadiyah Yogyakarta - Mohamad Deden Mutakin (Kreativasi : Journal of Community Empowerment, 2023)
A form of devotion of Madrasah Muallimin Muhammadiyah Yogyakarta to the community through the Mubaligh Hijrah Nasional (MHN) program is to produce a generation that is useful for society. The mosque was chosen as the location of the program, namely because the mosque is a building and institution that has a complex function in community service. The target of the MHN program is the congregation around the Darul Muttaqien Mosque Selomartani Kalasan Yogyakarta Special Region. The stages of implementing the MHN program are: preparation, socialization, implementation, monitoring and evaluation, and preparation of results reports. The results of the MHN program showed that the community felt that their spiritual needs were being met and encouraged the community to actively worship at the mosque through the programs that had been prepared.